2018
DOI: 10.1186/s13046-018-0919-8
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 inhibits the tumorigenesis and progression of hepatocellular carcinoma cells via upregulation of CYR61 expression

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most common malignant cancers with a high incidence and high mortality in East Asia. Identifying biomarkers and clarifying the regulatory mechanisms of HCC are of great importance. Herein, we report the role and mechanism of activating transcription factor 3 (ATF3), a member of the ATF/cAMP-responsive element-binding protein family of transcription factors in HCC.MethodsATF3 overexpression vector and shRNAs were transfected into HCC cancer cells to upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 44 publications
(46 reference statements)
2
52
0
Order By: Relevance
“…11 In contrast Chen et al reported that ATF3 inhibited hepatocellular carcinoma carcinogenesis. 12 However, the detailed molecular mechanisms of ATF3 in breast cancer tumorigenesis have not been characterized. In this study, we quantified the expression of ATF3 in breast cancer and investigated the effects of DNA methylation on ATF3 expression.…”
Section: Introductionmentioning
confidence: 99%
“…11 In contrast Chen et al reported that ATF3 inhibited hepatocellular carcinoma carcinogenesis. 12 However, the detailed molecular mechanisms of ATF3 in breast cancer tumorigenesis have not been characterized. In this study, we quantified the expression of ATF3 in breast cancer and investigated the effects of DNA methylation on ATF3 expression.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have reported oncosuppressive roles of ATF3. Its overexpression in liver cancer and hepatocellular carcinoma cells reduced proliferation and motility while apoptosis was increased [ 51 , 52 ]. Other reports showed ATF3 as inhibitor of invasion and migration both in colorectal cancer and ovarian cancer cells [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have reported 443 oncosuppressive roles of ATF3. Its overexpression in liver cancer and hepatocellular carcinoma 444 cells reduced proliferation and motility while apoptosis was increased 38,39 . Other reports 445 showed ATF3 as inhibitor of invasion and migration both in colorectal cancer and ovarian 446 cancer cells [40][41][42] .…”
Section: Reverse Phase Protein Array 358mentioning
confidence: 99%